Price-Wage Dynamics is A Transition Economy: The Case of Poland - Roberto Golinelli; Renzo Orsi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
In this paper we analyse the wage price relationship of an economy in transition characterized by important structural changes. It is known (see Perron 1989) that structural breaks in stationary time series can induce apparent unit roots. The stationarity analysis of the series employed in the present model is conducted jointly with the assumption that the breakpoint location is unknown. We follow a testing procedure recently proposed by Zivot and Andrews (1992). Cointegration analysis of wages and prices in presence of structural breaks permits to find empirical evidence in favour of two cointegration vectors involving prices and wages. Our analyses faces on the different structural behavior of price-wage dynamic relationship in the short and long run; we also enuncleate the relative importance of import prices as a source of wage-price short run fluctuations.
Keywords: 330